Ética e comunicação : prazeres fugazes, amores eternos, corpos sedutores e saudáveis na recepção dos discursos de Men s Health e Nova - Furtado, Pedro Calabrez (2009)
Our object is composed by the discourses contained in two Brazilian magazines: Men s Health and Nova. We approach the object through a transversal dialogue between the communication and social sciences fields and the philosophy of Michel Foucault. From this perspective, we suggest as a theoretical proposition that mass media influences its receptors subjective constitutions an influence upon the constitution of their individual self. This influence operates mainly through norms : internalized rules that guide the individuals in a natural-like fashion Men s Health and Nova, publications with prescriptive contents, are part of this operation. The norm, however, is not inescapable: Foucault offers an alternative to its objective restriction of our subjective identities: the dimension of ethics, an existential dimension in which we create our own selves through a free self-reflected intellectual exercise. After establishing our theoretical premises, we thoroughly investigate the way through which the magazines discourses operate (analyzing 6 issues of each one of them), defining what we called their physiology . Our aim is to answer the following problem: is there, in the reception of the discourses contained in these magazines, an ethical dimension? For that we interviewed 21 receptors, to find out that they conduct their lives in a complex power play that is strongly established upon norms, either to affirm or deny them. Men s Health and Nova operate along with many other social instances in a regime where its receptors think themselves based on pre-established criteria, where ephemeral pleasures are desired by some and criticized by all, while the ideal of eternal love is also a unanimous intention. At the same time, all value a specific kind of healthy body that is, at the same time, beautiful and sexy. None of that, though, is perceived though an exercise of self-reflection, free pondering. In other words, none of that comes from an ethical dimension